Diazoksit Yanıtsız Hiperinsülinemik Hipoglisemili Bir Olguda Tedavi ve İzlem - Damla Gökşen; Nurhan Murat; Özge Altun Köroğlu; Burçe Emine Yaşar; Samim Özen; Sanem Yılmaz; Mehmet Yalaz; Nilgün Kültürsay; Yeşim Ertan; Ahmet Çelik; Şükran Darcan (Galenos Yayinevi, 2017)
Hyperinsulinemic hypoglycemia (HH) is the most common reason for persistent and recurrent hypoglycemia in the neonatal and infancy periods. We presented a case diagnosed with HH on the first day of life and who underwent near-total pancreatectomy because of the unresponsiveness to the diazoxide treatment. Despite early diagnosis and management, complications developed due to hypoglycemia and surgery.